(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The purpose of this study was to investigate the pedagogical value of authentic documentaries as a scaffolding tool for developing intercultural sensitivity in senior secondary EFL students in Kazakhstan. The study was framed within stage-based models of intercultural competence and task-based media pedagogy, employing a 12-week intervention based on pre-viewing, while-viewing and post-viewing task cycles. One-group pretest-posttest quasi-experimental design with qualitative case study was used with two intact Grade 10-11 classes (N = 32). Quantitative data were collected using a modified and validated Intercultural Sensitivity Scale (ISS) and qualitative data were obtained from weekly reflection journals, video-assisted recall sessions (n = 12), and structured classroom observations. Paired-samples t-tests and reflexive thematic analysis were used in combination to measure progression through the ethnocentric to ethnorelative spectrum. The results indicated statistically significant improvements in overall intercultural sensitivity (t (31) = 8.34, p < .001, d= 1.47) especially in terms of respect for cultural differences and enjoyment of interaction. The qualitative data showed three ways that learning occurred: 1). Narrative transport which filtered out affect, 2). Multimodal awareness which enabled deconstruction of ideologies and 3). Mediated reflection which moved students from Minimization to Adaptation. This research offers a replicable, task-based pedagogical model that combines authentic visual data with critical pedagogy in the development of intercultural competence at the upper-secondary level. Suggestions are offered for curriculum development, instructional materials and media-based assessment, as well as limitations and recommendations for future study.